PENINGKATAN KOMPETENSI PETERNAK TERHADAP PENANGANAN KESEHATAN TERNAK DAN PEMBUATAN PAKAN FERMENTASI TERNAK DI DESA KETINDAN, KABUPATEN MALANG - bintari, intan galuh (Buletin Udayana Mengabdi, 2020)
The success of animal husbandry development will be largely determined by the human resources of the farmer as the main actor of the farm activity itself. Community Service Program is intended to help resolve problems faced by communities that are comprehensive, multi-sectoral, capable of guiding village communities towards a more prosperous life, creating a dynamic society, helping and improving the socio-economic conditions of citizens and facilitating citizens' access to information and Science. The purpose of organizing community service activities is to help solve the problems currently being faced by Farmer Groups, in this case are goat breeders in managing their business units. The implementation of community service consists of 3 activities namely coordination and planning of activities, training and evaluation of training results. Community Service Activities will take place in December 2019 at Ketindan village. Participants in the Community Service activity are goat farmers who are members of the Sumber Rejeki Farmer Group of 25 people. The results of the implementation of community service activities are expected that the community can apply the knowledge that has been given, namely handling animal health and making fermented feed (silage) which can be used to meet the needs of animal feed in Ketindan Village, Malang.   Keywords: Ketindan’s breeder, competency improvement, animal health, animal feed, silage.